Spinozism, Kabbalism, and Idealism from Johann Georg Wachter to Moses Mendelssohn - Mogens Laerke (Journal of Modern Philosophy)
The paper studies the historical background for the ‘idealist’ reading of Spinoza usually traced back to British and German Idealism. Here, I follow this history further back than and focus on one earlier idealist reading, indeed perhaps the mother of them all. It can be found in the Elucidarius cabalisticus, sive reconditae Hebraeorum philosophiae brevis et succincta recensio by Johann Georg Wachter, a kabbalist interpretation of Spinoza published in 1706. I am principally interested in the importance that Wachter’s book may have had for German philosophy in the second half of the eighteenth century. Focusing on Moses Mendelssohn’s Philosophische Gespräche of 1755, I argue that, via Mendelssohn, the Elucidarius cabalisticus is perhaps the earliest possible source of the idealist reading of Spinoza that dominated the German Spinozabild from throughout the Pantheismusstreit up to the second edition of Herder’s 1800 Gott: Einige Gespräche, culminating with Hegel’s ‘acosmist’ reading of Spinoza in the 1825–26 lectures on the history of philosophy.